Diversity and distribution of the deep-sea Atlantic Acanthocope (Crustacea, Isopoda, Munnopsidae), with description of two new species. (February 2018) - Malyutina, Marina V.; Frutos, Inmaculada; Brandt, Angelika
Abstract: The present paper provides data of the world-wide distribution, abundance and diversity of the rare deep-sea munnopsid genus, Acanthocope Beddard, 1885 and presents an identification key to the 18 known species of Acanthocope . Two new species, Acanthocope puertoricana sp. nov. from the tropical abyssal area near the Puerto Rico Trench and Acanthocope galaica sp. nov. from the Galicia Bank, Northeastern Atlantic are described. Additionally, Acanthocope annulatus Menzies, 1962 and Acanthocope eleganta Malyutina and Brandt, 2004 have been collected in the Puerto Rico Trench area, whereas Acanthocope galatheae Wolff, 1962 were collected along a latitudinal transect crossing the tropical abyssal North Atlantic during the Vema-TRANSIT expedition. A. puertoricana is most similar to A. carinata Chardy, 1972 from the Northwestern Atlantic and differs from the latter by: a more slender body; a broader head; a more slender and shorter lateral projections of the pleotelson; the presence of ventral spines on natasome; and a longer uropod. A. galaica sp. nov. is most similar to A. spinicauda Beddard, 1885 and differs from the latter by having a more elongate pleotelson with almost straight lateral margins between lateral spines, whereas the margins are more convex in A. spinicauda. Pereopods 5 and 6 of A. galaica have broader carpi than in A. spinicauda .